The use of computer graphics and virtual reality for visual impact assessments - Cox, Christopher (2003)
Changes to the visual character of the landscape can become a key issue capable of influencing the outcome of an Environmental Impact Assessment (EIA). These changes are commonly referred to as visual impact, and it is recognised, unlike many other aspects of EIAs, that Visual Impact Assessment (VIA) relies less upon measurement than upon experience and judgement (IEATLI, 1995). Currently, there are very few quantitative techniques for the evaluation of visibility and it is mostly assessed qualitatively since it is concerned with the human appreciation of the landscape (Zewe and Koglin, 1995 and Wherrett, 2002). The main problem with qualitative techniques in assessing visual impact is that they may lead to bias due to their inherent subjectivity, hence there is a need for a more structured and consistent approach towards VIA.